2021
DOI: 10.1038/s41372-021-00963-5
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin G in the treatment of ABO hemolytic disease of the newborn during the early neonatal period at a tertiary academic hospital: a retrospective study

Abstract: Objective To evaluate the efficacy and safety of intravenous immunoglobulin G (IVIG) in infants with ABO hemolytic disease of the newborn (HDN). Methods Infants with moderate-to-severe ABO HDN during early neonatal period (<7 days) at our hospital in 2017 were included in this retrospective study. Patients treated with IVIG and phototherapy were classified as the IVIG group, and those who only received phototherapy were classified as the phototherapy on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…The mechanism of IVIG is unclear, but it is thought that IVIG decreases hemolysis by blocking Fc receptors in the reticuloendothelial system and preventing the lysis of antibody-coated erythrocytes ( 12 , 13 ). Although several studies have suggested that IVIG was effective for treating neonatal hemolytic jaundice and decreasing the number of infants that require an exchange transfusion ( 14 18 ), some clinical studies found that IVIG treatment failed in the management of infants with ABO HDN ( 19 , 20 ). Recently, a Cochrane review found insufficient evidence to recommend the use of IVIG in alloimmune HDN ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of IVIG is unclear, but it is thought that IVIG decreases hemolysis by blocking Fc receptors in the reticuloendothelial system and preventing the lysis of antibody-coated erythrocytes ( 12 , 13 ). Although several studies have suggested that IVIG was effective for treating neonatal hemolytic jaundice and decreasing the number of infants that require an exchange transfusion ( 14 18 ), some clinical studies found that IVIG treatment failed in the management of infants with ABO HDN ( 19 , 20 ). Recently, a Cochrane review found insufficient evidence to recommend the use of IVIG in alloimmune HDN ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia and associated hyperbilirubinaemia in neonates are the most common clinical manifestations of HDN [5,20]. IVIG has been proposed as a potential intervention that can decrease the severity of haemolysis and the associated hyperbilirubinaemia.…”
Section: Discussionmentioning
confidence: 99%
“…ABO hemolitik hastalığı yenidoğan döneminde en sık görülen alloimmün hemolitik hastalıktır. ABO uygunsuzluğu anne-bebek çiftinin yaklaşık %25'inde, ABO hemolitik hastalık ise bebeklerin %1'inden azında görülmektedir (2). YHH'da antikor kaplı eritrositlerin retiküloendoteliyal sistemde yıkılması sonucu bebeklerde ciddi hiperbilirubinemi ve anemi gelişebilmektedir (1,3).…”
Section: Introductionunclassified